Comparative study between DHFR and DHPS genes in Plasmodium falciparum Plasmodium vivax and Plasmodium knowlesi isolated from Sabah - Nor Afizah Nuin (2016)
Malaria is one of the globally challenging parasitic infectious diseases. Treatment failure due to resistance in malaria parasites is an important factor in the effective treatment of malaria. Dihydrofolate reductase (dhfr) and dihydropteroate synthase (dhps) are two genes that encode the enzymes involved in the folate pathway targeted by antifolate drugs. This study was performed to compare molecular analysis of these two genes in three most prevalent human Plasmodium parasites in Sabah namely P. falciparum, P. vivax and P. knowlesi. The genes dhfr and dhps were amplified and sequenced from PCR confirmed single infection isolates of P. falciparum, P. vivax and P. knowlesi. The sequences were analysed using DNASTAR and MEGA6 softwares. Among 228 samples collected, 70 of them were P. falciparum positive, 11 were P. vivax, 5 were P. malariae and 67 P. know/esi monoinfection. DNA sequence alignment of dhfr gene among Sabah isolates was highly conserved in P. falciparum and P. vivax while P. knowlesi demonstrated polymorphisms in about 4% of the full-length pkdhfr. Meanwhile, the same rates were also observed in dhps gene of which P. fa/ciparum and P. vivax showed less number of nucleotide polymorphisms than in P. know/esi. Haplotyping analysis at positions which mutations significantly reduce antifolate drug sensitivity revealed identification of 4 pfdhfr-pfdhps (2.8% of AIRNI-SGKAA, 69.4% of ANRNI-SGKAA, 25% of ANRNI-SGKGA and 2.8% of ANRNL-SGTGA) while only 2 pvdhfr-pvdhps FRTNI-SAKAV (33.3%) and LRMTI-SGKAV (33.3%) type in the study areas. With respect to P. knowlesi, the dhfr orthologues haplotyping analysis showed wild-type sequence (ANSSI) at this locus. At present, there is no report in pkdhps gene mutation conferring resistance has been described in P. knowlesi. However, nucleotide polymorphisms observed in pkdhfr and pkdhps from Sabah isolates could have resulted from the selection of P. know/esi populations with drug resistance alleles under continuous drug pressure indicating the possible presence of human-to-human transmission. This study also shows a remarkably high prevalence of mutations linked to drug resistance in P. falciparum and P. vivax which highlights the molecular study of polymorphisms in dhfr and dhps genes remain as a useful tool to monitor the emergence and spread of antifolate drug resistance in malaria parasites from Sabah isolates.